Antoni Madaliński Generał Woysk Polskich. - Simon, Karol Antoni ( -1841) (Poznań i Berlin w Litografii K.A. Simona, 1829)
Przedstawia Antoniego Madalińskiego w półpostaci 3/4 w lewo, głowa 3/4 w prawo, w mundurze.